Um framework multitemático para coleta de informação geográfica produzida por voluntários - Michele Brito Pinheiro (2016)
Since the resources associated with the Web 2.0 had allowed ordinary people to publish content produced by themselves, there have been growing number of initiatives to gather geographic information produced by volunteers. In this model of crowdsourcing, citizens are seen as spatially distributed “sensors”, enabled to collect different kinds of data through these applications. However, challenges related to spatial coverage, quality and motivation of volunteers require creative and varied solutions for the development of data collection instruments. This work presents a framework for generating such instruments, designed to allow the user to choose between multiple functions to gather information and alternatives to spatially represented events, phenomena and geographic objects. The framework also provides resources to recognize and value the participation of volunteers. Interactively through the web, it is possible to create resources for collecting information on multiple themes without the need of programming. We present a case study aimed at collecting data on urban mobility as the framework application example.